2015
DOI: 10.1590/1413-785220152305145784
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients on Sick Leave With Carpal Tunnel Syndrome

Abstract: Objective: To report clinical and epidemiological characteristics and risk factors of patients with Carpal Tunnel Syndrome (CTS) on sick leave admitted in a University Hospital. Methods: This is a transversal study conducted with patients admitted sequentially over 18 years of age, without distinction of gender and race in the period between September and November 2014. Patients answered a questionnaire and underwent physical examination carried out by the authors. Results: Twenty-five patients were admitted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…If we look up the literature investigating the relation between obesity and CTS, it is mentioned that obesity is a risk factor for CTS in most of the studies [3,4,5]. De Azevedo et al [6] investigated the profile of patients on sick leave with CTS and reported obesity with a ratio of 44% among these patients [6]. Similar to these studies in this study we recorded that weight and height was significantly higher for patients with right CTS.…”
Section: Discussionsupporting
confidence: 83%
“…If we look up the literature investigating the relation between obesity and CTS, it is mentioned that obesity is a risk factor for CTS in most of the studies [3,4,5]. De Azevedo et al [6] investigated the profile of patients on sick leave with CTS and reported obesity with a ratio of 44% among these patients [6]. Similar to these studies in this study we recorded that weight and height was significantly higher for patients with right CTS.…”
Section: Discussionsupporting
confidence: 83%
“…In many studies, CTS has been more commonly reported in women. [15][16][17] Carpal tunnel syndrome initially affects the dominant hand and, then, involves the contralateral hand. Bilateral involvement was reported in 46.1 to 62% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our cohort resorted to taking sick leave (about one month in average over the past year), about 40 % were advised to change the job, and one-third applied for permanent work disability pension, although only a few were granted one (post-study information). As we could not find disability studies covering a similar working population on computers, we can only compare our data with the other working populations of other countries ( 120 , 121 , 122 , 123 , 124 , 125 ). In general, data on working disability related to CTS are scarce, and mainly concern those collected after surgical interventions ( 126 , 127 , 128 , 129 ).…”
Section: Discussionmentioning
confidence: 99%